Characterisation of a series of triarylmethane dyes as light harvesters for photo-electrochemical systems. (April 2015) - Ng, Chun Hin; Ohlin, C. André; Winther-Jensen, Bjorn
Abstract: A series of commercially available dyes were characterised by electrochemical, spectroscopic and computational methods. Several dyes, including Fuchsin Basic and Malachite Green were found to have properties that make them potential candidates for use in photo-electrochemical systems. The risks of combining different characterisation methods are also highlighted, namely the combination of thermodynamic reactions (electrochemical redox reactions), electronic transitions (optical spectroscopy) and the use of computational techniques to describe them. Highlights: Triarylmethane dyes are characterised via electrochemical, optical and computational methods. Comparison between the methods are discussed, errors and discrepancies are explored. The structure of the dye and its behaviour under redox are important considerations. Low-cost commercial dyes are analysed for photo-electrochemical applications. Amino-triarylmethane dyes exhibited reversible redox peaks and are potential candidates for photo-electrochemical systems.